2016
DOI: 10.1007/s12311-016-0787-8
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of the Olivocerebellar Pathway in Motor Learning and Motor Control. A Consensus Paper

Abstract: For many decades the predominant view in the cerebellar field has been that the olivocerebellar system's primary function is to induce plasticity in the cerebellar cortex, specifically, at the parallel fiber-Purkinje cell synapse. However, it has also long been proposed that the olivocerebellar system participates directly in motor control by helping to shape ongoing motor commands being issued by the cerebellum. Evidence consistent with both hypotheses exists; however, they are often investigated as mutually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 245 publications
(326 reference statements)
3
82
0
Order By: Relevance
“…The correlation between reduced IO excitability and impaired cerebellar motor learning in TMEM16B KO mice adds new evidence to support the theory that IO excitability and the subsequent climbing fiber impulses play a key role on the formation of cerebellar motor learning (Lang et al, 2017; Najafi and Medina, 2013). The prevailing view of cerebellar motor learning is that IO neurons relay movement error signals through climbing fiber spikes to cause synaptic modification in the cerebellar cortex, such as long-term depression (LTD) of parallel fiber to Purkinje cell synapses (Lang et al, 2017).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The correlation between reduced IO excitability and impaired cerebellar motor learning in TMEM16B KO mice adds new evidence to support the theory that IO excitability and the subsequent climbing fiber impulses play a key role on the formation of cerebellar motor learning (Lang et al, 2017; Najafi and Medina, 2013). The prevailing view of cerebellar motor learning is that IO neurons relay movement error signals through climbing fiber spikes to cause synaptic modification in the cerebellar cortex, such as long-term depression (LTD) of parallel fiber to Purkinje cell synapses (Lang et al, 2017).…”
Section: Discussionsupporting
confidence: 52%
“…The prevailing view of cerebellar motor learning is that IO neurons relay movement error signals through climbing fiber spikes to cause synaptic modification in the cerebellar cortex, such as long-term depression (LTD) of parallel fiber to Purkinje cell synapses (Lang et al, 2017). Recent studies have clearly shown that, during motor learning, the number of climbing fiber spikes and the duration of the bursts, which reflect IO excitable state, control the number of spikelets within a complex spike waveform and the duration of the complex spike responses in Purkinje cells (Coesmans et al, 2004; Mathy et al, 2009; Rasmussen et al, 2013; Yang and Lisberger, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the Purkinje cell simple spike activity could be viewed as constituting the sensory prediction [45, 46, 63] (although it may also contribute to the motor command), while the climbing fiber activity resulting in Purkinje cell complex spikes provides a representation of sensory prediction errors [6466], driving cerebellar learning. It should be noted that, although this model has been highly influential in theories of cerebellar-based learning, there remains considerable debate over the functional role of the climbing fiber signals and their interaction with simple spike activity [50, 64, 67]. Furthermore, recent physiological data in mice and rats suggest cerebellar modules vary in the firing rate of simple spike activity and exhibit plasticity tuned to different time intervals between parallel and climbing fiber inputs [20, 21, 68].…”
Section: Sensorimotor Coordination Prediction and Error-based Learningmentioning
confidence: 99%
“…Last, APs in CN neurons are generated by excitatory inputs. This was mentioned by Llinás & Mühlethaler (1988), further discussed by Gauck & Jaeger (2003) and summarized recently in Lang et al (2017).…”
Section: Introductionmentioning
confidence: 80%
“…This was mentioned by Llinás & Mühlethaler (), further discussed by Gauck & Jaeger () and summarized recently in Lang et al . ().…”
Section: Introductionmentioning
confidence: 99%